Corporate Social Responsibility Disclosure and Profitabilitas: Evidance From Indonesian Mining Companies - Natalina, Sri Anugrah; Zunaidi, Arif (Innovation Business Management and Accounting Journal, 2023)
In non-mining companies, CSR patterns are numerous in the form of social assistance, scholarships, or the development of city facilities. However, for mining companies, the concept of CSR is patterned back to a time, namely the concept of renewal or natural care. This type of research is both descriptive and quantitative, and the method used for linear regression is simple. A sample of six mining companies with a total of 30 financial statements Mining companies in Indonesia. The result of the hypothesis means that Ho is accepted and Ha is rejected; that is, CSR disclosure has no effect on the return on assets. The results of the coefficient of determination analysis (R square of 14.4%) show that CSR disclosure contributes to the return on assets with a contribution of 14.4%. The organization manages its legitimacy according to the type of its social contract with society. Another factor for CSR disclosures to mining companies in Indonesia is the presence of political costs. Another form of contract fees that can be explained is the attitude of managers towards disclosure of information.